1973
DOI: 10.1073/pnas.70.5.1468
|View full text |Cite
|
Sign up to set email alerts
|

Association of the r IIA Protein with the Bacterial Membrane

Abstract: The Escherichia coli cell envelope is modified after infection with wild-type phage T4. For example, the cells become resistant to lysis from without (1), can be lysis inhibited (2), exclude superinfecting T4 phage (3) and ghosts (4), become increasingly permeable to ions and other compounds (5-7), and increase their synthesis and hydrolysis of phospholipids (8)(9)(10). At least some of these functions are coded for by the phage, because specific phage mutants, such as r (11), spackle (12), ac (7), and imm (13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Possible interaction of the DD gene products with the host membrane. The DD genes 39, 52, and 60 are located in that region of the T4 genetic map which contains several other genes which have been shown either to modify the host membrane, such as rIIA (10) and rIIB (22, 29), or to have membrane related functions such as the ac gene (8,24) and gene t (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible interaction of the DD gene products with the host membrane. The DD genes 39, 52, and 60 are located in that region of the T4 genetic map which contains several other genes which have been shown either to modify the host membrane, such as rIIA (10) and rIIB (22, 29), or to have membrane related functions such as the ac gene (8,24) and gene t (16).…”
Section: Discussionmentioning
confidence: 99%
“…The burst sizes in these two cases were Total incorporation of [methyl-3H]thymidine into DNA. Samples were taken at 5,10,15,25,35,45,60, 75, and 100 min after infection of E. coli S/6. Infection was carried out with am mutants representative 6f the four DD genes and with gene 41 mutant amN57 and wild type as controls.…”
Section: Incorporation Of [Methyl-3h]thymidine Intomentioning
confidence: 99%
“…It is, however, partially functional in its interaction with the replication complex. ( Since the rII proteins are bound to the membrane (34)(35)(36) and to DNA (37), the rII-suppression of L171 implies that the conversion of "joint" into "recombinant" molecules occurs at the membrane. This implication is strengthened by the suppression of the rII-plaque morphology by some gene 32 (and ligase) mutations.…”
Section: Discussionmentioning
confidence: 99%
“…infection. Altematively, the late function may increase membrane fragility directly by modifying the membrane; changes in membrane composition after infection have been reported (11,12,15,21,34,46,51). Furrow and Pizer (15) have found that after T4 infection the relative rates of 32p; incorporation into phosphatidylglycerol and phosphatidylethanolamine were altered.…”
Section: -mentioning
confidence: 99%